Common mental disorders and associated factors among adult patients admitted in non-psychiatric wards of public hospitals in Harari regional State, Eastern Ethiopia - Hirko Assefa; Tilahun Ali; Ibsa Mussa; Tadesse Misgana; Dawit Abdi; Abinet Zewudie; Abdi Temesgen (BMC Psychiatry)
Abstract Introduction Common mental disorders represent psychiatric co-morbidity in medical illness, which leads to poor adherence to treatment, increased exposure to diagnostic procedures and the cost of treatment, longer hospital stay, and increasing the risk of complications that result in morbidity and mortality among patients admitted to non-psychiatric wards. There is a dearth of evidence related to the prevalence of common mental disorders and associated factors among adult patients admitted to non-psychiatric wards, particularly in the study area. This study aimed to assess the prevalence of common mental disorders and associated factors among adult patients admitted to non-psychiatric wards of public hospitals in the Harari region, eastern Ethiopia. Methods An institutional-based cross-sectional study was conducted among 640 randomly selected patients admitted to non-psychiatric wards from November 15 to December 15, 2022. A systematic random sampling technique was employed to select the study participants. Data were collected by interviewer-administered structured and semi-structured questionnaires. Self-report questionnaire (SRQ-20) was used to assess the presence of common mental disorders. The collected data were entered into Epi-data version 3.1 and exported to STATA version 14 for analysis. Bivariable and multivariable logistic regression were used to evaluate the association between independent and the outcome variable. Variables with a p-value < 0.05 were taken as statistically significant with an adjusted odds ratio and 95% confidence interval. Results The prevalence of common mental disorders among adult patients admitted to non-psychiatric wards was found to be 45.3%, with a 95% CI: of 41.3–49.2. Age 41–51 years (AOR = 1.732, 95% CI: 1.030, 2.913), age 51 and above (AOR = 2.429, 95% CI: 1.515, 3.894), staying at hospital for 1–2 weeks (AOR = 1.743, 95% CI: 1.065, 2.853), staying at hospital for more than 4 weeks (AOR = 2.12, 95% CI: 1.77, 3.29), history of mental illness (AOR = 5.841, 95% CI: 2.274, 15.004), stressful life events (AOR = 1.876, 95% CI: 1.206, 2.9196), current substance use (AOR = 1.688, 95% CI: 1.75, 2.650), and poor social support (AOR = 2.562, 95% CI:1.166, 5.629) were factors significantly associated with common mental disorders. Conclusion The prevalence of common mental disorders among patients admitted to non-psychiatric wards was high. It appears to be significantly associated with age, length of hospital stay, history of mental illness, stressful life events, current substance use, and social support. The study suggested that patients who are admitted to non-psychiatric wards should be screened for common mental disorders and its associated factors as part of routine inpatient care.